PENGARUH PENERAPAN PROGRAM BACA TULIS AL-QUR’AN (BTQ) TERHADAP MAHARAH AL-QIRA’AH SISWA KELAS VII MTS DDI KELURAHAN BARU KABUPATEN TOLITOLI - Nur Hijrah Syukriyani; Muh. Jabir; Zul Aini Rengur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Qur'an Reading and Writing Program (BTQ) on the maharah al-qira'ah (Arabic reading skills) of seventh-grade students at MTs DDI Kelurahan Baru, Tolitoli Regency. The low ability of students to read Arabic texts serves as the primary background of this research, in which the BTQ program, which has been consistently implemented at the madrasah, is presumed to contribute significantly to the improvement of students' Arabic reading competence. This study employs a quantitative approach with a causal design, involving all seventh-grade students as a saturated sample of 47 respondents. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis encompassed descriptive statistics, normality testing, homogeneity testing, and simple linear regression using SPSS software. The results indicate that the implementation of the BTQ program has a significant effect on students' maharah al-qira'ah, as evidenced by a t-value exceeding the t-table with a significance level below 0.05. These findings confirm that the BTQ program not only functions as religious guidance, but also serves as an effective instrument in developing students' Arabic literacy skills, while simultaneously contributing to the achievement of SDGs Goal 4 on inclusive and sustainable quality education.